Adequacy of the Simplified Version of the Tinnitus Handicap Inventory (THI-S) to Measure Tinnitus Handicap and Relevant Distress - Lee, Jae Hee (The Korean Audiological Society, 2014)
BACKGROUND AND OBJECTIVES: The Tinnitus Handicap Inventory (THI) often requires patients to devote their time to complete the questionnaire than they expect. Given that it limits the effectiveness of THI in a busy clinical practice that desires a quick and easy assessment of tinnitus handicap, this study evaluated clinical usefulness of a Simplified version of Tinnitus Handicap Inventory (THI-S) in measuring the severity of tinnitus handicap as well as predicting the psychological distress associated with tinnitus. SUBJECTS AND METHODS: A total of 129 outpatients suffering from tinnitus (61 with normal hearing and 68 with hearing loss) participated in this study. The responses of THI-S (10 items) and THI (25 items) were evaluated to quantify the subjective handicap of tinnitus. The self-perceived level of stress, anxiety, and depression of all participants was measured with a series of self-report questionnaires such as Korean version of Brief Encounter Psychosocial Instrument (BEPSI), State Trait Anxiety Inventory (STAI), and Beck Depression Inventory (BDI), respectively. All the questionnaire responses were analyzed using non-parametric analyses to examine the convergence, comparability, internal consistency reliability and validity of THI-S. RESULTS: The severity of tinnitus handicap and the relevant psychological distress greatly varied across individuals. The THI-S responses were comparable to original THI responses, regardless of hearing status of patients. The internal consistency of THI-S responses was found to be good for total score (Cronbach's α=0.83-0.91), with moderately high consistency for the emotional, functional, and catastrophic subscales. Significant (p<0.01) correlations of the THI-S with the THI (r(s)=0.95) as well as with the BEPSI, STAI, BDI questionnaires (r(s)=0.40-0.45) suggest that the THI-S questionnaire appeared to be useful to provide objective data of subjective tinnitus handicap as well as predict psychological distress. Three factors were extracted through factor analysis, which explained 73% of the total variance. CONCLUSIONS: Despite reducing the length of 25 items of THI to 10 items, the THI-S can be used as s a simple but reliable and valid tool for evaluating severity of tinnitus handicap as well as detecting its negative impact on psychological functioning.